Association of anemia and platelet activation with necrotizing enterocolitis with or without sepsis among low birth weight neonates: a case–control study - Jiang, Zhou; Ye, Guangyong; Zhang, Songying; Zhang, Long (Frontiers in Pediatrics, 2023)
Background：To evaluate the value of the proportionof large platelets (PLCR) and platelet crit (PCT) in predicting necrotizing enterocolitis (NEC) in low birth weight (LBW) neonates.Methods： A total of 155 LBW (< 2500 g) neonates with NEC admitted to the neonatal intensive care unit (NICU) of the hospital from January 1, 2017 to November 30, 2019 were included in the case group. According to the 1:3 case-control study design, a total of 465 LBW neonates without NEC (3 for each LBW neonate with NEC) in the NICU born ≤ 24 h before or after the birth of the cases were included in the control group.2 Results：During the study period, a total of 6946 LBW neonates were born, and 155 had NEC, including 9298 who also had sepsis. Neonatal sepsis was the most important risk factor and confounding factor for NEC in LBW neonates. Further stratified analysis showed that in LBW neonates without sepsis, anemia (P = 0.001, OR = 4.367, 95% CI: 1.853-10.291) , high PLCR (P<0.001, OR = 2.222, 95% CI: 1.633-3.023) , and high PCT (P = 0.024, OR = 1.368, 95% CI: 1.042-1.795) increases the risk of NEC, and the receiver operating characteristic curve area of PLCR was 0.739, the sensitivity was 0.770, the specificity was 0.610, and the cutoff value was 33.55.The data showed that 2/100 LBW neonates were prone to NEC, and stratified analysis of confounding factors of sepsis identified the risk factors of NEC in LBW neonates. This study first reported the significant value of PLCR in the early prediction of NEC occurrence in LBW neonates without sepsis.